Controlled decongestion by Reprieve therapy in acute heart failure: results of the TARGET‐1 and TARGET‐2 studies. (29th August 2019) - Biegus, Jan; Zymlinski, Robert; Siwolowski, Pawel; Testani, Jeffrey; Szachniewicz, Joanna; Tycińska, Agnieszka; Banasiak, Waldemar; Halpert, Andrew; Levin, Howard; Ponikowski, Piotr
Abstract : Aims: Safe and effective decongestion is the main goal of therapy in acute heart failure (AHF). In the non‐randomized, prospective TARGET‐1 and TARGET‐2 studies (NCT03897842), we investigated whether adding the Reprieve System® (which continuously monitors urine output and delivers a matched volume of hydration fluid sufficient to maintain the set fluid balance rate) to standard diuretic‐based regimen improves decongestion in AHF. Methods and results: The population consisted of 19 patients hospitalized with AHF (mean age 67 ± 10 years, 18 male, ejection fraction 34 ± 15%, median N‐terminal pro‐B‐type natriuretic peptide 4492 pg/mL). Patients served as their own controls: each patient underwent 24 h of standard diuretic therapy followed by 24 h of diuretics with Reprieve therapy (with normal saline used for matched volume replacement). The primary efficacy endpoint of actual fluid loss not exceeding the target fluid loss at the end of therapy was met in all 19 (100%) patients. The mean diuresis during Reprieve therapy was 6284 ± 2679 mL (vs. 1966 ± 1057 mL 24 h before therapy) and 2053 ± 888 mL (24 h after therapy) (both P  < 0.0001). At the end of therapy, patient global assessment improved from 7.7 ± 1.1 to 3.0 ± 1.3 points ( P  < 0.001), central venous pressure decreased from 15.5 ± 5.3 mmHg to 12.8 ± 4.8 mmHg ( P  < 0.05) and the median urine sodium loss was 9.7 [3–13] mmol/h. The Reprieve therapy was safe, systolic blood pressure remained stable, mean creatinine dropped from 1.45 ± 0.4 mg/dL to 1.26 ± 0.4 mg/dL ( P  < 0.001) and biomarkers of renal injury did not change during treatment. Conclusions: The Reprieve System in conjunction with diuretic therapy supports safe and controlled decongestion in AHF.